Sosialisasi Pentingnya ASI Esklusif Sampai Bayi Usia 6 Bulan - Mertisa Dwi Klevina; Aglis Andhita Hatmawan; Irmawati Mathar (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The occurrence of nutritional insecurity in infants is due to not only lack of food, but also because breast milk (ASI) is mostly replaced with bottle milk in a way and the amount does not meet the needs. The growth and development of infants is largely determined by the amount of breast milk obtained, including energy and other nutrients contained in the milk. Breast milk without other food ingredients can meet the needs of growth until the age of about four months.. In nation building, human quality improvement. Service Activities March 2022 The activity was attended by 25 pregnant and lactating mothers. The implementation of community service activities used is the dissemination of reproductive health in preparation for breastfeeding. The method used is the lecture method, question and answer method and games / quizzes. The result of this community service activity is the awareness of mothers to participate in socialization activities regarding reproductive health in preparation for pregnancy or breastfeeding. Some of the supporting factors for these activities include: 1. The participants have a great willingness to get information and knowledge about socialization regarding reproductive health as a preparation for breastfeeding, 2. This health education activity is strongly supported by the village, either directly or indirectly, actively participates in the implementation of health education regarding socialization of reproductive health as a preparation for breastfeeding.